Twelve tips for engaging students and community partners in medical education. (2nd December 2022) - Marjadi, Brahmaputra; Scobie, Jeff; Doyle, Kerrie; Tobin, Stephen; Whitton, Gilbert; Rollinson, Nathan; Haque, Shafiul; Fava, Grace; Smith, Mitchell; Spannenberg, Jennifer; Micheal, Sowbhagya
Abstract: There is increasing evidence on the positive outcomes of engaging students and community partners in medical education, especially in achieving social accountability. However, less is known about the steps through which these engagements are established. This paper outlines twelve tips on establishing a robust and enduring partnership with students and community partners in medical education, using examples from the Western Sydney University School of Medicine. While context is paramount in any engagement program, these tips are formulated to be transferable to medical education settings in different countries, education systems, and the broader context of health professional education.